Models of evaluating efficiency and risks on integration of cloud-base IT-services of the machine-building enterprise: a system approach; IOP Conference Series: Materials Science and Engineering; Vol. 124 : Mechanical Engineering, Automation and Control Systems (MEACS2015) - Razumnikov S. V. Sergey Viktorovich (Numerical Simulation of Applied Problems, 2016)
Title screen